Estudio de factibilidad para el desarrollo de una página web para la venta de productos ofrecidos en Novainser en Babahoyo - Zamora Espin, Darlen Eduardo (2021)
“Novainser” is a family business dedicated to the commercialization of multi-trade located in the city of Babahoyo since 2002; Over time, the company has grown both in its structure and in the lines it sells. As “Novainser” has short-term growth plans through expansion; The objective of this project is to evaluate the feasibility of developing a web page to see if sales increase, for which a market and financial study will be carried out. The methodology used in this project is a quantitative descriptive research, a survey of 10 questions will be carried out to people where the tastes and preferences, the socioeconomic profile and the consumption behavior of the surveyed population will be known, reflecting positive data to consider for “Novainser”, once the respective study has been carried out.